2015
DOI: 10.1517/14740338.2015.1073258
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiviral therapy for HIV and hepatitis C – drug interactions and side effects

Abstract: The safety profile of current DAA and the most recently approved ARV is quite favorable. Interactions between DAA and ARV could be frequent in clinical practice. The most common drug interactions affect drug metabolism by inducing or inhibiting the cytochrome P450 system, leading to abnormal drug exposures. Throughout this mechanism HCV and HIV protease inhibitors interact, especially when co-formulated with ritonavir as a pharmacoenhancer, and non-nucleoside HCV and HIV polymerase inhibitors. In contrast, HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 80 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…Through those mechanisms, it is reported that protease inhibitors for both HIV and HCV, such as asunaprevir, non‐nucleoside HCV and HIV polymerase inhibitors, interact. In contrast, comparatively newer HCV DAA and HIV ART, such as HIV and HCV nucleoside/nucleotide polymerase inhibitors, and most HCV NS5A inhibitors such as daclatasvir, and HIV integrase inhibitors rarely affect CYP450, suggesting that such drugs are free from significant drug interactions . In transplant recipients, further consideration of HIV ART, HCV DAA and calcineurin inhibitors must be taken into account .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through those mechanisms, it is reported that protease inhibitors for both HIV and HCV, such as asunaprevir, non‐nucleoside HCV and HIV polymerase inhibitors, interact. In contrast, comparatively newer HCV DAA and HIV ART, such as HIV and HCV nucleoside/nucleotide polymerase inhibitors, and most HCV NS5A inhibitors such as daclatasvir, and HIV integrase inhibitors rarely affect CYP450, suggesting that such drugs are free from significant drug interactions . In transplant recipients, further consideration of HIV ART, HCV DAA and calcineurin inhibitors must be taken into account .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, comparatively newer HCV DAA and HIV ART, such as HIV and HCV nucleoside/nucleotide polymerase inhibitors, and most HCV NS5A inhibitors such as daclatasvir, and HIV integrase inhibitors rarely affect CYP450, suggesting that such drugs are free from significant drug interactions. 20 In transplant recipients, further consideration of HIV ART, HCV DAA and calcineurin inhibitors must be taken into account. 1 In the present case, conversion from ETR to TDF might have led to a transient elevation of HIV RNA in week 16, which spontaneously recovered to normal levels within the next 4 weeks and did not recur.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 86 drugs have been approved for treatment of 17 viral infections [2]. However, some of these agents possess severe side effects [3][4][5]. For example, anti-HCV ribavirin causes hemolytic anemia when used long-term; anti-IAV zanamivir worsens breathing in patients with asthma; and anti-HIV drug, rescriptor, can cause severe rashes and lipodystrophy [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…(9,10) In addition, there are 10 million patients with HIV/AIDS worldwide co-infected with other viruses (e.g., hepatitis C virus, hepatitis B virus). (7,11,12) Antivirals against the co-infections could further increase the severity of liver toxicities and injuries. Currently, there is no consensus on how to manage patients with AIDS suffering from liver disease because the mechanisms underlying the hepatotoxicity of alcohol abuse and drugs are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…(7,11,13) The cellular stress responses are most relevant because both alcohol and anti-HIV drugs are metabolized in the liver, and this is bound to stress the liver. We and others reported that alcohol and/or anti-HIV drugs induced endoplasmic reticulum (ER) stress, lipid accumulation, and hepatic cell death.…”
Section: Introductionmentioning
confidence: 99%